3D DEM modeling of biocemented sand with fines as cementing agents. (24th November 2022) - Wu, Huanran; Wu, Wei; Liang, Weijian; Dai, Feng; Liu, Hanlong; Xiao, Yang
Abstract: Microbially induced calcium carbonate precipitation (MICP) has attracted much attention as a promising green technique for soil improvement. Despite the significance of precipitation pattern in mind, constitutive relations or numerical models considering the finite‐strain mechanical effects of the various precipitation patterns are rarely developed. In this paper, we propose a novel 3D DEM modeling scheme by using coarse particles to represent sand grains and fines as cementing agents, to reproduce the various precipitation patterns in MICP‐treated sand. Based on the topological relations with adjacent particles and the contribution to the mechanical improvement, the cementing fines are classified into effective, partially effective, surface coating, and pore filling ones. The microstructural characteristics and their evolution upon external loading are investigated quantitatively after a careful calibration and validation. The microstructural variation in experiments can be well reproduced, pinpointing this variation as a possible cause for the fluctuation in experimental data. Massive coating fines are produced accompanying the microstructural degradation, which is initiated by the breakage of effective bonds. The breakage of partially effective bonds may become dominating later in the medium to strong cemented specimens. One weakly cemented specimen shows diffuse failure with simultaneous bond‐breakage and friction. In contrast, the medium to strong cemented specimens show localized failure with the dominating mechanism transiting from bond‐breakage to friction producing notable pore filling fines. We propose a relation between unconfined compressive strength and the equivalent effective volume fraction of cementing agents normalized by the pretreatment porosity, which reveals the coupling effects of the initial configuration and the precipitation pattern on the mechanical improvement.